A comprehensive view on risk reporting: Evidence from supervisory data - Puriya Abbassi; Michael Schmidt (Deutsche Bundesbank, 2018)
We show that banks' risk exposure in one asset category affects how they report regulatory risk weights for another asset category. Specifically, banks report lower credit risk weights for their loan portfolio when they face higher risk exposure in their trading book. This relationship is especially strong for banks that have binding regulatory capital constraints. Our results suggest the existence of incentive spillovers across different risk categories. We relate this behavior to the discretion inherent in internal ratings-based models which these banks use to assess risk. These findings imply that supervision should include a comprehensive view of different bank risk dimensions.
Keywords: G01; G21; G28; 330; internal ratings-based regulation; credit risk; market risk; incentive spillovers; capital regulation; comprehensive risk assessment